2016
DOI: 10.1007/s12013-016-0738-5
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid-Dependent Conformational Changes in CRISPR–Cas9 Revealed by Site-Directed Spin Labeling

Abstract: In a type II Clustered-Regularly-Interspersed-Short-Palindromic-Repeats (CRISPR) system, RNAs derived from the CRISPR locus complex with the CRISPR-associated (Cas) protein Cas9 to form an RNA-guided nuclease that cleaves double-stranded DNAs at specific sites. In recent years, the CRISPR-Cas9 system has been successfully adapted for genome engineering in a wide range of organisms. Studies have indicated that a series of conformational changes in Cas9, coordinated by the RNA and the target DNA, direct the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Moreover, advances in techniques are noteworthy as site-directed spin labeling (SDSL), in combination with electron paramagnetic resonance (EPR) spectroscopy, has proven to be unique for characterizing protein topography, local and global structure, and dynamics regardless of complexities caused by enzyme-matrix signals and/or enzyme-matrix interactions. [37][38][39][40][41][42][43][44][45][46] Accordingly, the application of SDSL-EPR for mapping the host-guest interactions of the enzymes within various functional COF pores may be able to answer key questions about the impact of a confined spatial environment on the degree of freedom of the infiltrated enzyme and thereby the accompanying reactivity. These results are also anticipated to offer unique insight into the chemistry of the bespoke host environments in the COFs.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Moreover, advances in techniques are noteworthy as site-directed spin labeling (SDSL), in combination with electron paramagnetic resonance (EPR) spectroscopy, has proven to be unique for characterizing protein topography, local and global structure, and dynamics regardless of complexities caused by enzyme-matrix signals and/or enzyme-matrix interactions. [37][38][39][40][41][42][43][44][45][46] Accordingly, the application of SDSL-EPR for mapping the host-guest interactions of the enzymes within various functional COF pores may be able to answer key questions about the impact of a confined spatial environment on the degree of freedom of the infiltrated enzyme and thereby the accompanying reactivity. These results are also anticipated to offer unique insight into the chemistry of the bespoke host environments in the COFs.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, structural analysis and biochemical experiments have suggested that conformational plasticity of the protein underlies the processes of nucleic acid association and subsequent cleavage. 7,12,13 However, the conformational changes triggering the binding of the nucleic acids remain speculative. It is unclear, in fact, how the conformational plasticity of Cas9 would allow the transition from an “open” apo state to a “closed” conformation in which the protein binds its guide RNA and DNA target.…”
Section: Introductionmentioning
confidence: 99%
“…This structure is thought to depict a precatalytic state of the system (Cas9:pre-cat), given that a distance of ∼18 Å separates the catalytic H840 from the cleavage site on the t -DNA, suggesting that a further conformational transition is required for the formation of a catalytically competent Cas9. Overall, structural analysis and biochemical experiments have suggested that conformational plasticity of the protein underlies the processes of nucleic acid association and subsequent cleavage. ,, However, the conformational changes triggering the binding of the nucleic acids remain speculative. It is unclear, in fact, how the conformational plasticity of Cas9 would allow the transition from an “open” apo state to a “closed” conformation in which the protein binds its guide RNA and DNA target.…”
Section: Introductionmentioning
confidence: 99%
“…EPR in combination with spin trapping has been applied to detect the radicals formed during the initiation, propagation, and termination of polymerization and polymer degradation . EPR has also been applied to probe the structure and dynamics of macromolecules with arbitrary size, heterogeneity, and complexity, as demonstrated in polymers, proteins, and nucleic acids . Typical information from EPR measurements include long‐range (a few nm) intra‐macromolecular distance distributions and site‐specific conformational dynamics (ns to ms) .…”
Section: Introductionmentioning
confidence: 99%